A Pécsi Egyetemtörténeti Gyűjtemény - Dezső, Krisztina; F. Dárdai, Ágnes (Per Aspera ad Astra, 2016)
The University of Pécs and its predecessor institutions have already started the work around revealing and preserving the history between the two world wars: yearbooks, almanacs, works about the university history have been made. In connection with the academic anniversaries between 1967 and 1992 the collecting of the university history material also began. In 1992 an exhibition had been opened about the history of the medical training of the Medical University of Pécs, and in 2000 about the various detriments of the integrated University of Pécs, presented in the Vasváry House. The Pécs University History Collection 2010 was officially got the rank of public collection in 2010, and in this year the newly arranged, permanent interactive exhibition was opened. The five permanent exhibition halls of the exhibition guide the visitors through the medieval university in Pécs until today's modern university representing the history of higher education in Pécs. The main scope of activities of the University of Pécs History Museum is related to the processing and the history of the university documents, objects, numismatic and fine art, photographs, books and academic journals collection, and making these works available for the public. The institute’s wide collections of treasures are represented with the help of the databases and temporary exhibitions per year. (Translated by Dávid Molnár)